2016
DOI: 10.1186/s12958-016-0198-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-platelet therapy holds promises in treating adenomyosis: experimental evidence

Abstract: BackgroundRecently emerging evidence indicates that endometriotic lesions are wounds undergoing repeated tissue injury and repair (ReTIAR), and platelets induce epithelial-mesenchymal transition (EMT), fibroblast-to-myofibroblast transdifferentiation (FMT), leading ultimately to fibrosis. Due to the commonality of cyclic bleeding as in endometriosis, adenomyotic lesions are also wounds that undergo ReTIAR, and we have recently provided evidence corroborating platelet-induced EMT, FMT and fibrogenesis in adenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 78 publications
2
40
1
Order By: Relevance
“…In contrast to our findings with eSF from women without any gynecologic disorder, prolonged exposure of endometriotic and adenomyosis lesions to activated platelets results in fibrosis due to epithelial-to-mesenchymal transition, fibroblast-tomyofibroblast transdifferentiation, and repeated injury and healing [59,60]. These processes are mediated by TGF-β1 and activation of TGF-β/SMAD signaling pathway, and antiplatelet therapy in a mouse model was shown to decrease the burden of endometriosis and adenomyosis [61,62]. These data underscore baseline molecular differences between endometriotic/adenomyotic ectopic endometrial cells compared to eutopic endometrial cells from subjects without such pathology [36,63], resulting in different molecular and functional responses when exposed to activated platelets.…”
Section: Prp Stimulates Endometrial Cell Proliferation and Migrationcontrasting
confidence: 98%
“…In contrast to our findings with eSF from women without any gynecologic disorder, prolonged exposure of endometriotic and adenomyosis lesions to activated platelets results in fibrosis due to epithelial-to-mesenchymal transition, fibroblast-tomyofibroblast transdifferentiation, and repeated injury and healing [59,60]. These processes are mediated by TGF-β1 and activation of TGF-β/SMAD signaling pathway, and antiplatelet therapy in a mouse model was shown to decrease the burden of endometriosis and adenomyosis [61,62]. These data underscore baseline molecular differences between endometriotic/adenomyotic ectopic endometrial cells compared to eutopic endometrial cells from subjects without such pathology [36,63], resulting in different molecular and functional responses when exposed to activated platelets.…”
Section: Prp Stimulates Endometrial Cell Proliferation and Migrationcontrasting
confidence: 98%
“…We concluded that mifepristone effectively relieved dysmenorrhea symptoms for adenomyosis patients. Furthermore, it is reported that platelets played an important role in the development of adenomyosis and anti-platelet treatment could reduce uterine hyperactivity and improve generalized hyperalgesia [39]. Our data showed that mifepristone significantly decreased platelet count in serum of the adenomyosis patients.…”
Section: Discussionsupporting
confidence: 52%
“…Zhou et al ., 2016 investigated the effect of high- and low-dose anti-platelet therapy using a thromboxane A2 synthesis inhibitor (ozagrel) or platelet depletion therapy using the rat anti-mouse GPIbα polyclonal IgG antibody in an adenomyosis mouse model. Platelet activation is related to angiogenesis since its co-occurrence with TGF-β1 release leads to EMT and fibroblast-to-myofibroblast transdifferentiation.…”
Section: Resultsmentioning
confidence: 99%